2022
DOI: 10.1039/d2an01185a
|View full text |Cite
|
Sign up to set email alerts
|

A deep clustering-based mass spectral data visualization strategy for anti-renal fibrotic lead compound identification from natural products

Abstract: We present a deep clustering-based MS data visualization strategy (MCnebula), integrated with the influential open-source automatic MS annotation platform SIRIUS and in vivo and in vitro methods, to screen and validate potential lead compounds from natural products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Thus, reducing excess levels of glutamate in the synaptic cleft is a potential strategy for preventing and treating neurologic diseases [ 35 , 36 ]. Since oxidative stress and neuroinflammation are common pathologic signatures of neurodegeneration, PD might possess neuroprotective effects, as PD exhibits a series of promising therapeutic potential, such as anti-inflammatory and antioxidative activity [ 13 , 14 , 15 , 16 , 17 ]. In this work, we observed that PD inhibited the 4-AP-evoked release of glutamate in association with Ca 2+ -dependent synaptic vesicular exocytosis and VDCCs rather than by modulating the plasma membrane potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, reducing excess levels of glutamate in the synaptic cleft is a potential strategy for preventing and treating neurologic diseases [ 35 , 36 ]. Since oxidative stress and neuroinflammation are common pathologic signatures of neurodegeneration, PD might possess neuroprotective effects, as PD exhibits a series of promising therapeutic potential, such as anti-inflammatory and antioxidative activity [ 13 , 14 , 15 , 16 , 17 ]. In this work, we observed that PD inhibited the 4-AP-evoked release of glutamate in association with Ca 2+ -dependent synaptic vesicular exocytosis and VDCCs rather than by modulating the plasma membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…hongyao and Lagotis integra W. W. Smith [ 8 , 9 , 10 , 11 , 12 ]. Previous studies have shown that PD exhibits a series of impressive pharmacological effects, such as inhibitory activity against angiotensin-converting enzyme, an anti-renal fibrosis effect, cardioprotection, anti-inflammatory activity, and antioxidative activity [ 13 , 14 , 15 , 16 , 17 ]. Compounds with anti-inflammatory and antioxidative properties might confer neuroprotective effects, considering that oxidative stress and neuroinflammation are essential elements of neuronal death in various neurodegenerative disorders [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%